Strict Liability Principles Regulation on Corporate Crimes in Environmental Pollution & Strengthening Criminal Penalties in Indonesia - Candrawati, Ni Komang Ayu; Kurniawan, I Gede Agus (Jurnal Daulat Hukum, 2025)
Corporations as legal subjects have great potential to cause environmental pollution, especially in the era of increasingly massive industrialization. Legal protection for the environment in Indonesia was initially strengthened through the application of the strict liability concept in Article 88 of the Environmental Protection and Management Law (UU PPLH). However, since the enactment of the Job Creation Law, the principle of absolute responsibility has experienced significant degradation, which has an impact on weak law enforcement against corporations that pollute the environment. This study aims to analyze in detail the legal regulations for corporate crimes in cases of environmental pollution in Indonesia, with a focus on significant changes after the enactment of the Job Creation Law and their impact on environmental protection efforts and justice for affected communities. This study used a normative juridical method with a statutory approach and a conceptual approach. Data are analyzed qualitatively by examining laws and regulations, court decisions, legal doctrines, and relevant literature. The results of the study show that the elimination of the phrase “… without the need for proof of guilt …” in Article 88 of the PPLH Law by the Job Creation Law has weakened the application of the strict liability principle, making it more difficult for business actors to be held legally accountable. This has the potential to increase environmental damage because the burden of proof is now shifted back to the victim. As a result, substantive justice for the community and the effectiveness of environmental protection are increasingly threatened. In addition, the presence of PP No. 22 of 2021 and Law No. 6 of 2023 emphasizes legal uncertainty and opens loopholes for corporate actors to avoid criminal responsibility.